HKALE Pure Maths 2001 Paper01

# I find r ii let e be the intersection of ab and cd

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: s) (b) If v = λa + µb , where λ, µ ∈ R and λ , µ ≠ 0 , and v is also a linear combination of vectors c and d , show that λ : µ = (−b ⋅ c × d) : (a ⋅ c × d) . Hence evaluate λ : µ . (5 marks) (c) Suppose the four points A , B , C and D are coplanar. (i) Find r . (ii) Let E be the intersection of AB and CD . Using (b) or otherwise, find BE : EA and the position vector of E . (7 marks) 2001-AL-P MATH 1−9 −8− Go on to the next page 13. (a) Let P( x) = x 4 + ax 3 + bx 2 + cx + d where a, b, c, d ∈ R . (i) Show that if α is a complex root of P(x) = 0 , then α is also a root of P(x) = 0 . (ii) For any α ∈ C , show that ( x − α )( x − α ) is a quadratic polynomial in x with real coefficients. Hence show that P(x) can be factorized as a product of two quadratic polynomials with real coefficients. (6 marks) (b) Let f(x) = x 4 + 8 x 3 + 23 x 2 + 26 x + 7 and g(x) = f(x + k) where k ∈ R and the coefficient of x 3 in g(x) is zero. (i) Find k and the coefficients of g(x) . (ii) Suppose g(x) = ( x 2 + px + q)( x 2 + rx + s) where p, q, r, s ∈ R . By comparing coefficients or otherwise, show that p 6 − 2 p 4 + 5 p 2 − 4 = 0 . Hence find p , q , r and s . (iii) Find all roots of f(x) = 0 . (9 marks) 2001-AL-P MATH 1−10 −9− (a) If a , b are two real numbers such that a ≤ 1 ≤ b , show that a + b ≥ ab + 1 and the equality holds if and only if a = 1 or b = 1 . (3 marks) (b) 14. Show by induction that if x1 , x 2 , ! , x n are n (n ≥ 2) positive real numbers such that x1 x 2 " x n = 1 , then x1 + x 2 + " + x n ≥ n and the equality holds if and only if x1 = x 2 = " = x n = 1 . (6 marks) (c) Let a1 , a 2 , ! , a n be n (n ≥ 2) positive real numbers. Using (b) a1 + a 2 + " + a n n ≥ a1 a 2 " a n and the n equality holds if and only if a1 = a 2 = " = a n . (3 marks) or otherwise, show that (d) For u ≥ 0 and n = 2, 3, 4, ! , using the identity (1 + u ) n − 1 = u[(1 + u ) n −1 + (1 + u ) n −...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online